Pengaruh Fasilitas Belajar Siswa Terhadap Hasil Belajar Siswa - Annisa Meliyana; Amir Arham; Meyko Panigoro; Radia Hafid; Roy Hasiru; Sudirman Sudirman; Maya Novrita Dama (State University of Gorontalo, 2023)
The study aimed to determine the influence of learning facilities on the student learning outcomes in class VII in in the integrated social sciences subject at SMP Negeri 03 Wonosari, Boalemo regency. Moreover, this study used aquantitative approuchwith explanatory research method. In collecting the data it used a questionnaire with a population of 38 student at SMP Negeri 03 Wonosari. The sampling technique used total sampling which requed the members of the population to be used as samples. Furthermore, in analyzing the data, there were instrument tests classical asumption tests, hypotesis testing,and simple linier regression test used in this study. To conclude, the learning facilities improved students’ learning outcomes at SMP Negeri 03 wonosari, Boalemo Regency. Meanwhile, the rest was influenced by other variable which were not explained in this study